Market Risk Measurement of Sharia Stock Portfolios Using Monte Carlo–Based Var: Evidence From An Indonesian Sharia Insurance Company - Wahri Irawan; Mochamad Indrajit Roy; Fitri Raya; Ikin Ainul Yakin; Rustamunadi Rustamunadi (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2026)
This study aims to evaluate the investment risk of PT A's sharia stock portfolio during the period of May-August 2025 using the Value at Risk (VaR) approach. The research sample consists of nine stocks listed in the Sharia Securities List (DES), comparing the Parametric VaR and Monte Carlo Simulation methods in measuring the aggregate risk of cross-sector portfolios. The results show that the Monte Carlo approach produces risk estimates that are more responsive to abnormal return distributions and contain fat tail phenomena compared to the parametric method. Based on validity testing (backtesting), the Monte Carlo VaR model is statistically valid at a 95% confidence level with a VaR value of −2.74%, but it is not valid at a 99% confidence level because it fails to capture extreme price movements. These findings indicate that even though diversification has been applied, PT A's portfolio risk remains higher than the sharia market risk due to weight concentration in volatile sectors such as petrochemicals and minerals. Therefore, 95% VaR is recommended as the basis for determining daily operating capital reserves in order to maintain the Risk-Based Capital (RBC) ratio above the minimum regulatory limit set by the Financial Services Authority of 120%, while continuing to supplement risk measurement through additional risk mitigation in extreme market conditions.